Wet granular matter : a truly complex fluid - Herminghaus, S. (Stephan) (Series in soft condensed matter, 2013)
This is a monograph written for the young and advanced researcher who is entering the field of wet granular matter and keen to understand the basic physical principles governing this state of soft matter. It treats wet granulates as an instance of a ternary system, consisting of the grains, a primary, and a secondary fluid. After addressing wetting phenomena in general and outlining the basic facts on dry granular systems, a chapter on basic mechanisms and their effects is dedicated to every region of the ternary phase diagram. Effects of grain shape and roughness are considered as well. Rather than addressing engineering aspects such as existing books on this topic do, the book aims to provide a generalized framework suitable for those who want to understand these systems on a more fundamental basis.